Temporomandibular Joint Surgical Reconstruction and Managements - Kummoona, Raja (IntechOpen, 2023)
Temporomandibular Joint - Surgical Reconstruction and Management is an outstanding book that deals with recent advances in the surgical and therapeutic management of temporomandibular disease. The book discusses the most difficult diseases of the TMJ including ankylosis of the joint in both adults and children. The series of operations carried out for the treatment of first arch syndrome, and recent techniques advocated by the editor for dislocation and subluxation are described. Among the therapeutic and diagnostic tools used and advocated by the authors are the electronic stethoscope for the detection of disc movements and hypermobility of the joint, and orthodontic treatment for the correction of occlusions and to eliminate pain in the joint. This book is highly recommended to all surgeons practicing TMJ surgery, including oral,maxillofacial, craniofacial and ENT surgeons, neurosurgeons, and postgraduate students.